The Impact of Digital Transformation on Business Performance: A Study of Pakistani SMEs - Mubarak, M. F.; Shaikh, F. A.; Mubarik, M.; Samo, K. A.; Mastoi, S. (Engineering, Technology & Applied Science Research, 2019)
Business ecosystems are continuously evolving. In this hyper-competitive era, firms are increasingly transforming their business operations through advanced digital technologies. Gone are the days of mere testing and debating the influence of digital transformation and industry 4.0, yet the time has come for actionable steps. Therefore, this study has identified the role of industry 4.0 technologies including big data, cyber-physical systems, internet of things and interoperability, on the performance of Small and Medium-sized Enterprises (SMEs) in Pakistan. A relevant questionnaire was developed and distributed randomly in the cities of Karachi, Lahore, Peshawar, Islamabad, Gujrat, and Sialkot. After applying multiple regression techniques through SPSS, it was found that big data, cyber-physical systems, and interoperability have a significant positive impact to improve business performance, while the insignificant effect of internet of things was revealed. Since the research in the area of digital transformation and industry 4.0 is scant, the current study has contributed novel directions, insights and a framework for future researchers. Moreover, this study will help managers to justify the allocation of resources towards technological infrastructure development in the operations of their firms. Finally, policymakers will find it helpful in order to devise suitable strategies for developing human capital and to enhance their absorptive capacity.